2000
DOI: 10.1093/pubmed/22.3.427
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study to establish the prevalence of urinary symptoms and felt need in the community: the Leicestershire MRC incontinence study

Abstract: Urinary symptoms are very common in adults over 40 years of age living in the community. However, symptom-based estimates probably overestimate the level of need for health care in the community. It may be more effective and efficient to target services, in the first instance, on those people who report clinically significant symptoms that are bothersome or socially disabling. A consensus on thresholds and definitions of urinary symptoms is required to standardize clinical and research work and to target servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
138
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 40 publications
10
138
1
2
Order By: Relevance
“…In women, urinary incontinence is estimated to affect nearly 50% of middle aged and older women, leading to significant distress, limitations in daily functioning, and poorer quality of life (8,9). Diabetes has been identified as an important independent risk factor for incontinence in several large observational studies, including the Nurses' Health Study, and is associated with 30 -100% increased risk (9 -12).…”
Section: Bladder Dysfunction In Womenmentioning
confidence: 99%
“…In women, urinary incontinence is estimated to affect nearly 50% of middle aged and older women, leading to significant distress, limitations in daily functioning, and poorer quality of life (8,9). Diabetes has been identified as an important independent risk factor for incontinence in several large observational studies, including the Nurses' Health Study, and is associated with 30 -100% increased risk (9 -12).…”
Section: Bladder Dysfunction In Womenmentioning
confidence: 99%
“…Using this definition it is clear that nocturia is frequent among the adult population. In a UK study of 2074 women aged ≥ 19 years Swithinbank et al [9] found a prevalence rate of 16%, while another UK study [10] found that 20% of men and 21% of women aged > 40 years had nocturia. A study in the USA among a population aged ≥ 60 years showed prevalence rates for men of 25% and for women of 24% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic floor dysfunction (PFD), mainly including stress urinary incontinence (SUI), pelvic organ prolapse (POP), and fecal incontinence (FI), is common in women and more prevalent in the aging population [1][2][3]. PFD is a complex disease that involves many factors, and the majority of research suggests that the total collagen content is decreased in pelvic connective tissue and that the pelvic support tissues (the ligament, muscle and fascia) are relaxed because of reduced collagen fibers, which eventually leads to PFD [4,5].…”
Section: Introductionmentioning
confidence: 99%